Regional brain metabolism as the predictor of performance on the Trail Making Test in schizophrenia. A 18FDG PET covariation study - Horacek, Jiri; Dockery, Colleen; Kopecek, Milan; Spaniel, Filip; Novak, Tomas; Tislerova, Barbora; Klirova, Monika; Palenicek, Tomas; Höschl, Cyril (Neuro endocrinology letters, 2006)
OBJECTIVES: With the aim to indicate the functional anatomical substrate of cognitive dysfunction in schizophrenia we evaluated the relationship between resting brain metabolism and performance on the Trail Making Test (TMT). As the prerequisite analysis we compared the performance in Part A and B of the TMT between schizophrenic patients and controls. Resting brain metabolism was investigated by (18)FDG positron emission tomography (PET) as the probe for the relative regional synaptic strength and density. METHODS: (18)FDG PET data were analyzed by SPM99 with TMT A and B as the covariate (p< or =0.001). RESULTS: Schizophrenic patients (N=42) had worse performance in both TMT A and B compared to controls (N=42). In schizophrenic subjects (18)FDG PET did not predict the performance on Part A (psychomotor speed) but predicted that for Part B (set-shifting and flexibility) of the TMT. The (18)FDG uptake in the superior, middle and inferior frontal gyruses bilaterally was associated with better performance in the TMT B. The negative covariation between 18FDG uptake and time spent in the TMT B was detected in the temporal and parietal cortices, pre- and postcentral gyruses, precuneus limbic regions (anterior cingulate, uncus) and the pons. CONCLUSIONS: Our data indicate that hypometabolism in the frontal lobes and hypermetabolism in the temporo-parieto-limbic regions is the neurobiological basis for deficient TMT B performance in schizophrenia.
Keywords: Fluorodeoxyglucose F18; mozek; Humans; lidé středního věku; mapování mozku; Frontal Lobe; Trail Making Test; čelní lalok; schizofrenie; Female; dospělí; fluorodeoxyglukosa F18; lidé; test cesty; Schizophrenia; Basal Metabolism; Brain Mapping; Adult; ženské pohlaví; Male; Middle Aged; Brain; Adolescent; Psychomotor Performance; Positron-Emission Tomography; mužské pohlaví; bazální metabolismus; pozitronová emisní tomografie; psychomotorický výkon; mladiství